Geriatric Oral Ulcers: Frequency and Major Risk Factors - Nabiha Farasat; Javaria Saeed; Muhammad Ilyas; Muhammad Saim; Muhammad Saeed (Proceedings)
Introduction: The oral epithelium provides a protective barrier to injuries. Not only the aging process but some systemic conditions cause atrophy of oral epithelium making it sensitive to mechanical injuries and the occurrence of oral lesions. Recognition and proper cure of oral lesions are important for the quality of life of geriatric and crucial parts of total oral health care.